Evaluation of anticancer effects of cerium oxide nanoparticles on mouse fibrosarcoma cell line. Issue 4 (6th September 2018) - Nourmohammadi, Esmail; Khoshdel-sarkarizi, Hoda; Nedaeinia, Reza; Sadeghnia, Hamid Reza; Hasanzadeh, Leila; Darroudi, Majid; Kazemi oskuee, Reza
Abstract: Cerium oxide nanoparticles are associated with anticancer effects. While protecting normal cells, these nanoparticles exert their anticancer effects via oxidative stress and apoptosis in the cancer cells. In this study, the anticancer properties of nanoceria on fibrosarcoma cell line are evaluated. Cerium oxide nanoparticles were synthesized by the coprecipitation method and their anticancer effects on mouse fibrosarcoma tumor cells (WEHI164) were investigated. Viability assay was evaluated by MTT, and the DC‐FDA assay performed for the detection of reactive oxygen species. For apoptosis assay, the annexin V/PI test was done as well as measuring the mRNA and protein expression levels of Bax and Bcl2 by real‐time PCR and western blot method, respectively. Characterization of nanoceria reveals that synthesized nanoceria has cubic floruit structure with a size of about 30 nm. Toxicity assessment results show that nanoceria increases ROS levels and induced apoptosis in a dose‐dependent manner in cancer cells (WEHI164), whereas low levels of toxicity were observed in normal cells (L929), even at the concentrations above 250 µg/ml in MTT assay. Real‐time PCR and western blot assays showed that nanoceria could significantly increase the Bax expression in cancer cells. The results showed that nanoceria could act as a potential therapeutic agent for the treatment of fibrosarcoma. Abstract : Nanoceria had innate toxicity on cancer cells and can be used as a novel therapeutic agent for the treatment of fibrosarcoma, whereas protecting the normal cells from oxidative stress by reducing free radicals in them. These unique properties make nanoceria a fascinating nanoparticle that can be used in medicine.